Peran Penting Work Life Balance dan Kompensasi dalam Employee Retention: Studi Karyawan Generasi Z di Unit Kantor Cabang BRI Lenteng Agung - Nabilla Fauziah; Syifa Fitri Fairus; Agung Surya Dwianto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The company has several aspects to run the Employee Retention program, such as implementing a Work-Life Balance system and providing compensation to employees. The purpose of this research is to analyze the important role of Work Life Balance and Compensation in Employee Retention (Study of Generation Z Employees at BRI Lenteng Agung Branch Office Unit). This research method is quantitative. This research uses interview and observation techniques to solve the problems found. The informants of this research consisted of 2 (two) generation Z employees and 1 (one) supervisor employee. This research data collection technique is by observation and interview. The results of this study are that work-life balance and compensation have an important role in the sustainability of employee retention at the BRI Lenteng Agung branch office unit. The company has implemented a balance of time for work life and personal life for its employees, and the company also provides compensation in accordance with company policy where this has a positive impact on employees and is included in the company's efforts to retain employees. This is supported by the statements of two informants who are generation Z employees and a supervisor who explained that the working hours, workload, and organizational culture as well as the compensation provided by this company are able to make them stay in the position they are currently in, until later they will follow the increase in position or career path in the future.